Poles in Latvian Republic as a Positive Example of Mutual Acquisition of Cultures - Olga V. Raina (Publishing house "Sreda", 2019)
The purpose of the article is to present a historical and cultural review of the fourth largest national minority living in the territory of modern Latvia, namely the Polish ethnic group. Based on the comparative historical method, the issues of preserving the identity of the Poles, as well as their role in the history, scientific life and cultural life of the country, are considered. As a result of this work, the facts of the interpenetration of Polish and Latvian cultures were revealed, which the author considers as a positive factor for the coexistence of different peoples in a multi-ethnic environment. It is concluded that the lack of hostility and hostility of the ethnic majority towards national minorities living in the territory of their state is extremely positive and has a significant contribution to the further formation and development of the nation.